PERENCANAAN STRUKTUR ATAS GEDUNG SEKOLAH MTsN III KABUPATEN PASAMAN - Fadlan, Muhammad; Bastian, Elfiani; Putra, Yorizal; Zulhedi, Zulhedi (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Planning for the Upper Structure of the MTsN III School Building in Pasaman Regency aims to have a building with good capacity and quality that meets the Indonesian National Standard (SNI). This plan plans the construction of a building structure to achieve a plan that is strong, safe, and fulfills the requirements set out in the regulations that apply to building structure planning. The Planning of the Upper Structure of the MTsN III School Building in Pasaman District was a preliminary design using SAP2000. Loads that are input into SAP2000 are dead loads, live loads, building's own weight, earthquake loads. From the preliminary design results, the results obtained are beam reinforcement (B1) size 30 x 50 with concrete quality 250 MPa, steel quality 420 Mp, reinforcement used 18D19, beam (B2) size 25 x 40 with reinforcement used 16D19, column size 40 x 40 the reinforcement used is 12D19, the floor slab uses D10 reinforcement with a floor plate thickness of 13 cm, stirrup reinforcement D10, the thickness of the concrete cover is 40 mm. From the planning above, it can be concluded that it has fulfilled the terms and conditions in Indonesian regulations and standards.Keywords: Structure of Beams, Columns, Floor Slabs, Loading, Reinforcement.